About prognostication of coefficients of heat conductivity and linear heat expansion multicomponent komposites - Скачков, В.А.; Баглюк, Г.А.; Воденникова, О.С.; Иванов, В.И. (Problems of Tribology, 2014)
There are developed the models of prognostication for coefficients of heat conductivity and linear heat expansion of multicomponent metalcarbon composite materials of the tribotechnical function. The calculations of there of thermophysical parameters and experimental verification of the got results are executed.